KEPUASAN PASIEN TERHADAP KUALITAS PELAYANAN BPJS PADA RUMAH SAKIT DEWI SARTIKA KOTA KENDARI - Muh. Elwan, La Ode (REZ PUBLICA, 2019)
The purpose of this study was to determine patient satisfaction with BPJS service quality at Dewi Sartika General Hospital, Kendari City. The method used in this research is descriptive using a qualitative approach.The results showed that patient satisfaction with BPJS service quality at Dewi Sartika General Hospital, Kendari City was quite good. From the results of the study, it was concluded that patient satisfaction with BPJS service quality at the Dewi Sartika General Hospital in Kendari City was quite good and fulfilled expectations by showing the dimensions of service quality, where patient satisfaction is seen from service quality indicators. If the quality of the service is good and good enough then the patient will feel satisfied with the service provided.Â